Soliton models of dislocation and acoustic emission in metallic materials - PAWEŁEK, A.; PILECKI, S. (Archives of Acoustics, 2000)
In this paper the analysis of the dislocation models and the possibilities of their application to the description of the acoustic emission (AE) sources, which are acting during plastic deformation of metallic materials are presented. Especially the one-dimensional atomic Frenkel-Kontorova model pf dislocation (model FK) has been discussed with particular reference to its nonlinear properties which determine the movement of the dislocation kink along the dislocation line as a solitary wave process. At the same time the equivalence of the FK model with the string model of dislocation (S model) has been demonstrated. In consequence, the FK model has been generalized by the consideration of new terms of higher order responsible for the anharmonic (nonlinear) interaction between the atoms (including also the second coordination zone). A new class of nonlinear partial differential equations (NLPD equations), which may play a role in the theory of lattice vibration of the crystal with dislocation as well as in the theory of dislocations, has been obtained. The results are discussed in the context of rich experimental data (obtained at IMIM) which establish the correlations between the measured AE parameters and the plastic deformation mechanisms as well as microstructure evolution occurring in fcc single and polycrystals subjected to channel-die compression, especially at the liquid nitrogen temperature.